Effects of supplemental calcium and vitamin D on the APC/β‐catenin pathway in the normal colorectal mucosa of colorectal adenoma patients. Issue 2 (14th June 2016) - Liu, Siyu; Barry, Elizabeth L.; Baron, John A.; Rutherford, Robin E.; Seabrook, March E.; Bostick, Roberd M.
Abstract : APC/β‐catenin pathway malfunction is a common and early event in colorectal carcinogenesis. To assess calcium and vitamin D effects on the APC/β‐catenin pathway in the normal‐appearing colorectal mucosa of sporadic colorectal adenoma patients, nested within a larger randomized, double‐blind, placebo‐controlled, partial 2 × 2 factorial chemoprevention clinical trial of supplemental calcium (1200 mg daily) and vitamin D (1000 IU daily), alone and in combination versus placebo, we assessed APC, β‐catenin, and E‐cadherin expression in colon crypts in normal‐appearing rectal mucosa biopsies from 104 participants at baseline and 1‐yr follow up using standardized, automated immunohistochemistry and quantitative image analysis. For vitamin D versus no vitamin D, the ratio of APC expression to β‐catenin expression in the upper 40% (differentiation zone) of crypts (APC/β‐catenin score) increased by 28% ( P = 0.02), for calcium versus no calcium it increased by 1% ( P = 0.88), and for vitamin D + calcium versus calcium by 35% ( P = 0.01). Total E‐cadherin expression increased by 7% ( P = 0.35) for vitamin D versus no vitamin D, 8% ( P = 0.31) for calcium versus no calcium, and 12% ( P = 0.21) for vitamin D + calcium versus calcium. These results support (i) that vitamin D, alone or in combination with calcium, may modify APC, β‐catenin, and E‐cadherin expression in humans in directions hypothesized to reduce risk for colorectal neoplasms; (ii) vitamin D as a potential chemopreventive agent against colorectal neoplasms; and (iii) the potential of APC, β‐catenin, and E‐cadherin expression as treatable, pre‐neoplastic risk biomarkers for colorectal neoplasms. © 2016 Wiley Periodicals, Inc.